PENGARUH KUALITAS KREDIT YANG DIKLASIFIKASIKAN TIDAK PRODUKTIF SEKTOR KONSTRUKSI TERHADAP TINGKAT KESEHATAN KREDIT PADA BANK JABAR BANTEN CABANG BEKASI - Didin Rasyidin Wahyu (Gapenas Publisher, 2021)
Banks as financial institutions whose activities include collecting funds from the public in the form of deposits such as savings , deposits , demand deposits and other forms of savings and channel them back to the community in order to improve the living standard of the people in the form of loans / credit . Bank may also be regarded as an institution that won the trust of the public , so the public trust must be maintained , then the bank must satisfy the clients as much as possible in carrying out its activities both in service , fund raising and distribution , financial information and other services in the field . Bank Jabar Banten as banking and business institutions as one of the fittings has a mission and local autonomy as a function of (a) Driving and driving the pace of development in the area , (b) Holders of Local Cash and / or implementing storage area is money, (c) One Local revenue sources . Based on the mission and functions carried the Bank Jabar Banten, in order to participate in promoting the pace of development continues, Bank Jabar Banten loans / credits to employers, employees, the propesi, and others